Original paperAssessment of the influence of licochalcone on selected functional skin parameters in patients with impaired vasomotor disorders and rosacea - Broniarczyk-Dyła, Grażyna; Prusińska-Bratoś, Magdalena; Kmieć, Małgorzata L. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction: Rosacea is a dermatosis of 0.2-2% of the population which occurs in both sexes, although more often in women. The onset of illness usually occurs after 30 years of age, rarely before. It occurs in four forms. One of them is erythemato-telangiectatic rosacea, which is characterized by paroxysmal transient change in the type of skin redness (pre-rosacea) associated with vascular hyperreactivity. Persistent changes may be a diffuse erythema and telangiectasia, accompanied by a burning sensation and burning skin. Among others, flavonoids are used in the treatment of rosacea. Aim : To evaluate the impact of the flavonoid licochalcone, a component of creams – soothing moisturizer designed for day and night for a soothing effect in patients with vasomotor disorders and patients with rosacea. Material and methods : The study group included 35 patients (31 women and 4 men) aged from 30 years to 60 years (average age 48.3 years). Twenty patients had pre-rosacea and 15 rosacea skin lesions. Before the enrolment of patients in the study, in 20 patients after 6 and 8 weeks and 15 patients after 8 weeks of application of the preparations, the severity of erythema, visible on the skin, skin hydration and transepidermal water loss (TEWL) were assessed using the Courage-Khazaka equipment. Results: A significant reduction in the severity of erythema after 6 and 8 weeks of treatment with the creams was demonstrated. A significant increase in the degree of hydration of the epidermis and the reduced average value of TEWL were observed. Conclusions : The use of creams containing licochalcone in patients with pre-rosacea and rosacea helps to reduce the severity of erythema. These creams also affect the reduction in TEWL values and increased hydration of the epidermis.